2021
DOI: 10.1111/pai.13542
|View full text |Cite
|
Sign up to set email alerts
|

Do allergic clinical manifestations increase the risk of behavioral problems in children? A cross‐sectional study

Abstract: Background: Children with allergic clinical manifestations tend to have behavioral or emotional problems such as hyperactivity or worse mental health. However, previous studies on this association did not adequately adjust for confounders like parenting stress, demographic characteristics, or allergy presentation. This study aimed to investigate the relationship between childhood allergic clinical manifestations and behavioral problems, adjusting for confounders such as demographic characteristics, parenting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Using the PASS15 program for the calculation of the minimal sample size required for our survey. The prevalence of behavioral problems in the control group estimated from previous literature was 20% [14], and the case group with an expected OR = 1.5 [5,15], the ratio of case to control was 1:2, assuming α = 0.05 and β = 0.10, the results showed that we need 306 cases. If the information of about 10% participants in the case group were unavailable in this survey, the total of sample size in the case group reached 337.…”
Section: Sample Size Calculationmentioning
confidence: 75%
See 1 more Smart Citation
“…Using the PASS15 program for the calculation of the minimal sample size required for our survey. The prevalence of behavioral problems in the control group estimated from previous literature was 20% [14], and the case group with an expected OR = 1.5 [5,15], the ratio of case to control was 1:2, assuming α = 0.05 and β = 0.10, the results showed that we need 306 cases. If the information of about 10% participants in the case group were unavailable in this survey, the total of sample size in the case group reached 337.…”
Section: Sample Size Calculationmentioning
confidence: 75%
“…Several previous studies have shown that the association between childhood asthma and behavioral problems was unclear. Part of the LIFE Child study that included 2701 participants, a prospective longitudinal cohort study showed that bronchial asthma was associated with internalizing problems, but not with externalizing behavioral problems like attention-de cit, hyperactivity disorder and ADHD [4,5]. Furthermore, some reports highlighted that asthma was a liated with more behavioral problems [6].…”
Section: Introductionmentioning
confidence: 99%
“…The interested reader will find recent articles published in Pediatric Allergy and Immunology on similar issues related to food allergy. [4][5][6]…”
Section: Editorial Comments On: "Food-allergy-specific Anxiety and Di...mentioning
confidence: 99%
“…This thorough and comprehensive compilation will be a very useful resource for clinicians and future studies and represents an important step in developing standardized methods for assessing and monitoring food allergy–related anxiety in both clinical populations and research settings. The interested reader will find recent articles published in Pediatric Allergy and Immunology on similar issues related to food allergy 4–6 …”
mentioning
confidence: 99%
“…Известно, что риск поведенческих нарушений у детей прямо связан с длительностью периодов обострений АР [9,11]. Для прогноза течения заболевания в целом, а также риска осложнений имеет значение не только тяжесть, но и длительность периодов обострений, и быстрота начала экстренной терапии [1,4,5,12].…”
Section: Introductionunclassified